Optothermally Tuned Charge Transfer Plasmons in Au-Ge2Sb2Te5 Core-Shell Assemblies. (5th March 2018) - Gerislioglu, Burak; Ahmadivand, Arash; Pala, Nezih
ABSTRACT: Tunable plasmonic resonances across the visible and near infrared spectra have provided novel ways to develop next-generation nanophotonic devices. Here, by utilizing optothermally controllable phase-changing material (PCM), we studied highly tunable charge transfer plasmon (CTP) resonance modes. To this end, we have designed a two-member dimer assembly including gold cores and Ge2 Sb2 Te5 (GST) shells in distant, touching, and overlapping conditions. We successfully demonstrated that toggling between amorphous (dielectric) and crystalline (conductive) phases of GST allows for achieving tunable dipolar and CTP resonances along the near-infrared spectrum. The proposed dimer structures can help forming optothermally controlled devices without further morphological variations in the geometry of the design, and having strong potential for advanced plasmon modulation and fast data routing.